KEMAMPUAN PSEUDOMONAS BERFLUORESEN SEBAGAI AGEN ANTAGONIS TERHADAP Ralstonia solanaceaerum PENYEBAB LAYU TANAMAN NILAM (Pogestemon cablin Benth) - Abil Pratama Putra; Linda Advinda; Moralita Chatri; Dezi Handayani (Universitas Cokroaminoto Palopo, 2026)
Patchouli (Pogestemon cablin Benth) is a cultivated plant that can produce oil and generate income for farmers. However, attacks by plant pests (OPT) often pose a challenge to patchouli production in Indonesia. One organism that causes wilt disease in patchouli plants is the bacterium Ralstonia solanaceaerum. Therefore, more environmentally friendly and sustainable control methods are needed. One strategy is the use of biological agents, especially antagonistic rhizosphere bacteria such as fluorescent pseudomonas. This study was conducted from June to August 2025 at the Plant Physiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. This study used a completely randomized design (CRD) as the experimental design. In this study, there were 6 treatments (different isolates), each repeated 3 times. The parameter observed was the formation of an inhibition zone using the disc diffusion method. The data were analyzed using analysis of variance (ANOVA). If there were significant differences, Duncan's New Multiple Range Test (DNMRT) was used at a 5% level. Based on the results and discussions, it can be concluded that all fluorescent Pseudomonas isolates tested have the ability to inhibit R. solanaceaerum, the cause of wilt disease in patchouli plants. The isolate with the best ability to inhibit the growth of R. solanaceaerum on patchouli plants was isolate Pf S36 with an inhibition zone of 20.37 mm, but there was no significant difference between the other isolates because the inhibition effectiveness was relatively uniform.